Temporal changes in carbon dioxide exchange rates, acetylene reduction and distribution of nitrogen in Barrel Medic (Medicago trunculata Gaertn.) grown in the field - Alston, AM; Puckridge, D.W. (Commonwealth Scientific and Industrial Research Organisation, 1986)
Barrel medic (cv. Jemalong) was grown on a red-brown earth at Adelaide to examine dry matter production and nitrogenase activity in relation to environmental conditions and carbon dioxide exchange. At 4-10-day intervals, measurements were made of dry weight and nitrogen content in plant parts, and mineral nitrogen content of the soil. Rates of acetylene reduction and carbon dioxide exchange, and environmental variables were measured. Curves fitted to data for solar radiation and carbon exchange rate were used to calculate daily values for net carbon dioxide uptake. Estimates of dry weight production derived from these net uptakes of carbon dioxide gave a similar curve to measured dry weight, but overestimated maximum dry weight by almost 20%. The difference is presumed to be due to materials lost from the roots. At maturity, dry weight and plant nitrogen content had declined by 10 and 14% respectively from their maxima of 1.02 kg m-2 and 26.1 g m-2 in October. All fractions of the plant except the litter and seed lost nitrogen. Rates of acetylene reduction reached a maximum of 39 mmol m-2 day-1 104 days from sowing, when the medic began to flower, and declined to almost zero by 145 days. At this time carbon dioxide exchange rates were high, and the plants were still accumulating nitrogen; from approximately 14 g N m-2 at day 104 to 24 g N m-2 at day 145. These changes are discussed in relation to environmental conditions and soil nitrogen content.